2021
DOI: 10.3390/ijerph18179017
|View full text |Cite
|
Sign up to set email alerts
|

Improving Construction Industrialization Practices from a Socio-Technical System Perspective: A Hong Kong Case

Abstract: Construction Industrialization (CI) tends to improve industrial performance and contributes substantially towards global sustainability. Considering these merits, many countries and regions, including Hong Kong, have released policies to promote CI uptake. However, those policy interventions ignore the dynamic influence of stakeholders and technologies, which significantly influence the efficient management of CI. In response, this study aimed to objectively depict a real socio-technical system of CI uptake ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 70 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…Scaling up the industrialized construction would effectively satisfy the affordable housing supply and meet the climbing demand, especially in metropolitan cities like HK [ 16 ]. Considering the superior performance of CI in housing developments, although, under different construction environments and different social conditions, various regions have released relevant policies on compulsory regulations and incentive schemes to promote CI uptake [ 17 ].…”
Section: Background Of Ci-related Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaling up the industrialized construction would effectively satisfy the affordable housing supply and meet the climbing demand, especially in metropolitan cities like HK [ 16 ]. Considering the superior performance of CI in housing developments, although, under different construction environments and different social conditions, various regions have released relevant policies on compulsory regulations and incentive schemes to promote CI uptake [ 17 ].…”
Section: Background Of Ci-related Policiesmentioning
confidence: 99%
“…Since HK is one of the most densely populated megacities in the world, housing supply is a crucial factor in its sustainable development [ 18 ]. With the overwhelming demand for high-quality, affordable housing in HK over recent years, the HK government has implemented compulsory regulations and incentive schemes to adopt CI [ 17 ]. As for manifestations of CI, prefabricated concrete components (PCCs), were first applied in public housing developments in the 1960s, where a 16-story public housing block was constructed with precast concrete panels [ 19 ].…”
Section: Background Of Ci-related Policiesmentioning
confidence: 99%
“…Jeong et al [122] evaluated accident cases that occurred in prefabricated construction projects in the United States and indicated that the familiar working environment, less high-altitude operations, and less exposure to bad weather were significantly beneficial to ensure occupational safety and health in modular projects. Their opinion echoed the arguments proposed by [123]. Murali and Sambath [123] also believed that the reduction of construction dust, noise, and other pollutants in prefabricated construction sites only protected the workers but also the surrounding communities.…”
Section: Social Sustainability 431 Occupational Safety and Healthmentioning
confidence: 81%
“…The development of Chinese construction industrialization is promoted by the macro development and the government, as well as a self-driven process [10]. However, those policy interventions ignore the dynamic influence of stakeholders and technologies, which significantly influence the efficient management of construction industrialization [11]. That is to say, the policy factor plays a dominant role, while the management factor and market factors are also significant [12].…”
Section: Introductionmentioning
confidence: 99%